Răspuns :
[tex]\it 5\cdot\left(x-\dfrac{8}{15}\right)=\dfrac{7}{3} \Rightarrow x-\dfrac{8}{15}=\dfrac{7}{3}:5 \Rightarrow x-\dfrac{8}{15}=\dfrac{7}{3}:\dfrac{5}{1} \Rightarrow x-\dfrac{8}{15}=\dfrac{7}{3}\cdot\dfrac{1}{5} \Rightarrow\\ \\ \Rightarrow x-\dfrac{8}{15}=\dfrac{7}{15} \Rightarrow x=\dfrac{7}{15}+\dfrac{8}{15} \Rightarrow x=\dfrac{7+8}{15} \Rightarrow x=\dfrac{15}{15} \Rightarrow x = 1[/tex]
[tex]5 \times (x - \frac{8}{15}) = \frac{7}{3} \\ \\ 5(x - \frac{ {2}^{3} }{3 \times 5}) = \frac{7}{3} \\ \\ 5( \frac{(3 \times 5)x + {( - 2}^{3}) }{3 \times 5}) = \frac{7}{3} \\ \\ 5( \frac{15x + ( - 8)}{3 \times 5}) = \frac{7}{3} \\ \\ \frac{5(15x - 8)}{3 \times 5} = \frac{7}{3} \\ \\ \frac{15x - 8}{3} = \frac{7}{3} \\ \\ 15x - 8 = 7 \\ \\ (15x - 8) + 8 = 7 + 8 \\ \\ 15x - 8 + 8 = 15 \\ \\ 15x = 15 \\ \\ \frac{15x}{15} = \frac{15}{15} \\ \\ x = 1 [/tex]